2010
DOI: 10.4103/0971-6203.71760
|View full text |Cite
|
Sign up to set email alerts
|

Indoor radon survey in a university campus of Nigeria

Abstract: CR-39 tracketch detectors were used for the measurement of 222Rn concentration in 24 offices in Nigeria’s oldest university campus in order to estimate the effective dose to the occupants from 222Rn and its progeny. The dosimetric measurements were made over a period of 3 months. Questionnaires were distributed and analyzed. The radon concentration ranged from 157 to 495 Bq/m3, with an arithmetic mean and standard deviation of 293.3 and 79.6 Bq/ m3, respectively. The effective dose to the workers was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…To date, several field studies measuring radon and/or its decay products have been conducted. The result obtained in this study is somewhat similar to that reported by Obed et al [ 12 ] in a university community in Ibadan a contiguous city to Ile-Ife but a bit higher than what was obtained in one of the studies done in a Ghanaian modern sandcrete building where the mean concentration was about 0.1 pCi/L. The mean values obtained at different floors also differed [ 16 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…To date, several field studies measuring radon and/or its decay products have been conducted. The result obtained in this study is somewhat similar to that reported by Obed et al [ 12 ] in a university community in Ibadan a contiguous city to Ile-Ife but a bit higher than what was obtained in one of the studies done in a Ghanaian modern sandcrete building where the mean concentration was about 0.1 pCi/L. The mean values obtained at different floors also differed [ 16 ].…”
Section: Resultssupporting
confidence: 89%
“…It has therefore become necessary to investigate work environment for elevated radon levels. As far as the published scientific literature is concerned, only one study has been conducted on the threat radon poses to public health in houses in Nigeria [ 12 ], even though a study on the radon soil gas has been conducted in Ile-Ife [ 13 ]. The interest in radon became urgent because of the known interest in cancer which has heightened in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The institution in Ondo State (72.21 Bqm -3 ) was observed to have the highest mean radon concentration while the lowest value was recorded for the tertiary institution assessed in Lagos State (48.28 Bqm -3 ). -3 which was lower than mean level of 284 Bqm -3 reported in some offices of Nigeria oldest University (Obed et al, 2010). The variation observed in the results recorded for the offices of the different institutions were largely due to the lithology feature on which each building was constructed as well as the age of the building.…”
Section: Radon Concentrationcontrasting
confidence: 55%
“…An international publication reported the extent of current knowledge about the health effects of inhaled 222 Rn and its progeny and made recommendations for the control of 222 Rn exposure in both dwellings and workplaces [3]. Several studies were conducted on 222 Rn levels in workplaces [4,5]. In the current study we also aimed to measure 222 Rn levels in the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Obed et al[4] measured222 Rn concentrations at a university campus in Nigeria in order to estimate the effective dose: only 24 offices were studied and the 222 Rn concentrations ranged from 157 to 495 Bq/m 3 .Furthermore, the effective dose to the workers was estimated and varied from 0.99 to 3.12 mSv/y, with a mean of 1.85 mSv/y. This value is less than what was obtained in the present work.Oikawa et al [4] performed 222Rn measurements from 2000 to 2003 at 705 sites in four categories: office, factory, school, and hospital.…”
mentioning
confidence: 99%